Measurement of the transverse momentum spectra of weak vector bosons produced in proton-proton collisions at s√=8 TeV - Khachatryan,V; Sirunyan,AM; Tumasyan,A; Adam,W; Asilar,E; Bergauer,T; Brandstetter,J; Brondolin,E; Dragicevic,M; Eroe,J; Flechl,M; Friedl,M; et al. (Journal of High Energy Physics, 2017)
The transverse momentum spectra of weak vector bosons are measured in the CMS experiment at the LHC. The measurement uses a sample of proton-proton collisions at s√=8 TeV, collected during a special low-luminosity running that corresponds to an integrated luminosity of 18.4 ± 0.5 pb−1. The production of W bosons is studied in both electron and muon decay modes, while the production of Z bosons is studied using only the dimuon decay channel. The ratios of W− to W+ and Z to W differential cross sections are also measured. The measured differential cross sections and ratios are compared with theoretical predictions up to next-to-next leading order in QCD.